Ultrasonics in clinical audiometry - Rama Mohan Babu P (Journal of All India Institute of Speech and Hearing, 1971)
Several investigators (Wegal 1932) Wever and Lawrence (1954); Deetherageet al, (1954), Corso and Oda (1961), Haaff and Knox (1963) have reported onhuman auditory responses to sounds of frequencies even above 10,000 HZ andupto 100,000 HZ. Corso (1965) while studying the phenomenon of high frequencyand ultrasonic hearing obtained DLS for pitch and loudness at variousfrequencies both by air and bone conduction. Even as evidences of cochlearfunction at high and ultrasonic frequencies are being obtained clinicians havestarted speculating about the possible uses of hearing in these frequencies as adiagnostic tool. The purpose of this article is to discuss (1) the problems involvedin the production, transmission and calibration of sonic and ultrasonic sounds(2) some of the studies made on the pitch and loudness discrimination functionsof cochlear at high and ultrasonic frequencies and finally (3) some of the possibleuses of these frequencies in the diagnosis of auditory impairments.